Analisis Pendapatan dan Margin Pemasaran Dalam Saluran Distribusi Beras Kabupaten Sidenreng Rappang - Aksal Mursalat; Bahtiar Herman; Reza Asra; Nining Triani Thamrin (AGRIMOR, 2022)
Sidenreng Rappang Regency is one of the providers of rice in South Sulawesi Province and makes it the main commodity. The problems faced by farmers in distributing their crops include farmers who are always in a position that does not benefit from the market mechanism. In addition, the selling price of grain is very low while the costs incurred by farmers have not been able to cover the production costs which of course will have an impact on the welfare of farmers and a decrease in the amount of rice production. The purpose of the study was to determine the model of the implementation of the rice distribution channel and to find out how much the income level and marketing margin of rice in Sidenreng Rappang Regency were. Informants who fit the research needs are 20 respondents who are rice farmers with an area of 1 ha and marketing institutions involved in distributing rice to the hands of final consumers. Some of the marketing agencies involved are 2 collectors, 1 rice miller, 1 wholesaler, and 1 retailer. This study uses a qualitative descriptive analysis method to determine rice's distribution channel while quantitative analysis analyzes the income and marketing margins of rice in Sidenreng Rappang Regency. The results showed that implementing the rice distribution channel system in Sidenreng Rappang Regency started with farmers, collectors, and rice milling companies and then distributed to two business actors, namely large companies and retailers to the last level to consumers. The average income earned by rice farmers per planting season with a land area of 1 ha is Rp. 23,745,000. The marketing margin obtained by each distribution agency is high for wholesalers to consumers of Rp. 7,750/kg, then the margin for retailers to consumers is Rp. 7,400/kg, followed by milling margins to retailers and wholesalers with values of Rp. 3,700/kg and Rp. 3,400/kg.